Recent Echocardiography Parameters for Predicting Better Functional Result after Mitral Valve Correction Surgery in Patients with Primary Mitral Regurgitation - Indah Puspita; Amiliana M Soesanto; Estu Rudiktyo; Rina Ariani; Ario Suryo Kuncoro (The Indonesian Heart Association, 2021)
Abstract Objectives We analyzed whether some echocardiographic parameters are good predictors of functional result after mitral valve correction surgery. Background Ejection fraction was not the only parameter to decide optimal time for surgery, nor an indicator for a better functional result after surgery. Severity measurement being a main consideration in surgery decision. Reduced left ventricle dimension after surgery reflect a better functional result. Methods In 2019, 67 patients was included in this analysis. Age 53 (17-67) years, male 52,2%. All patients are with severe primary mitral regurgitation and treated by mitral valve surgery (mitral valve repair or replacement). Retrospective echocardiographic analysis was performed, to find the best parameter for predicting better functional outcome after surgery. Results Data was collected from January to December 2019. From 262 primary mitral valve surgery underwent in National Heart Center Harapan Kita, there was 67 patients included, the other was excluded due to probability of secondary mitral regurgitation mechanism, concomitant congenital heart disease and or other significant valves disease, missing post-surgery data due to referral flow to the prior hospital and less complete echocardiographic views for further analysis. In bivariate analysis, end-diastolic volume (EDV) and regurgitant volume (RV) were strong predictor of decreasing left ventricle diameter after surgery (p 0.0001 and p 0.05). End-diastolic volume 133,5 ml or more is predictive for decreasing left ventricle diameter if surgery was conducted (sensitivity 87.3%, sensitivity 66.7%). Conclusions EDV and RV found to be good predictors for functional outcome of primary mitral valve surgery than other echocardiographic parameters. Measuring EDV before deciding timing of surgery will be helpful in targeting better functional result after surgery.